Spin Hall Effect Enhancement of Transmitted Light Through an Anisotropic Metamaterial Slab - Tingting Tang; Yanfen Zhang; Jie Li; Li Luo (IEEE Photonics Journal, 2017)
We study the spin Hall effect (SHE) enhancement of transmitted light through an anisotropic metamaterial slab. Physical mechanism of large transverse shift is explained based on the coupling between spin angular momentum and orbit angular momentum. Theoretical analysis predicts large transverse shift of transmitted light can be realized by four possible combinations of real or imaginary z component of the wave vectors, which is verified by simulation results. The anisotropy of metamaterial brings greatly enhanced SHE of transmitted light but the metamaterial loss and dispersion will reduce the transverse shift significantly. A maximum transverse shift of 15.24 μm (12λ) can be achieved in an anisotropic metamaterial of ZnGaO/ZnO multilayer without any amplification method.